2022
DOI: 10.3390/ijms23073576
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Positively Regulates Both Dark- and Age-Induced Leaf Senescence by Reducing ROS Accumulation and Modulating Abscisic Acid and Auxin Biosynthesis in Cucumber Plants

Abstract: Melatonin (MT), as a signaling molecule, plays a vital role in regulating leaf senescence in plants. This study aimed to verify the antioxidant roles of MT in delaying dark- or age-induced leaf senescence of cucumber plants. The results showed that endogenous MT responds to darkness and overexpression of CsASMT, the key gene of MT synthesis, and delays leaf senescence stimulated by darkness, as manifested by significantly lower malonaldehyde (MDA) and reactive oxygen species (ROS) contents as well as higher ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…It acts as an antioxidant and detoxifies ROS and RNS by enhancing the antioxidant enzyme activity under stress conditions [13]. Melatonin act as a promoter of seed germination [14] and lateral root formation [15], regulates flowering [16], and delays leaf senescence [17] to manage and control plant growth and development under challenging environments.…”
Section: Introductionmentioning
confidence: 99%
“…It acts as an antioxidant and detoxifies ROS and RNS by enhancing the antioxidant enzyme activity under stress conditions [13]. Melatonin act as a promoter of seed germination [14] and lateral root formation [15], regulates flowering [16], and delays leaf senescence [17] to manage and control plant growth and development under challenging environments.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin treatment increased the levels of IAA in rice and governed root architecture by the upregulation of auxin-related genes ( Liang et al., 2017 ). Acting as a powerful antioxidant, melatonin alleviated leaf senescence by increasing IAA levels via upregulating the expression of genes involved in IAA biosynthesis and signalling in cucumber plants ( Jing et al., 2022 ). The results of our study revealed that melatonin increased the expression of genes involved in IAA biosynthesis including AeYUC s, AeTRA , and AeMES , as well as the auxin response genes ( AeSAUR s) in okras after harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous melatonin is also associated with the overexpression of CsASMT (a key gene for melatonin synthesis), which can delay the senescence of dark-stimulated leaves. A greenhouse study on cucumbers reported that melatonin inhibited leaf senescence by reducing ABA biosynthesis and inhibiting its signaling pathway, while promoting IAA biosynthesis and its signaling pathway [ 108 ]. In apple, melatonin promotes the formation of adventitious roots, mainly by promoting IAA levels and up-regulating MdWOX11 in the stress induction stage [ 109 ].…”
Section: Relationships Between the Melatonin And Iaa Pathwaysmentioning
confidence: 99%